In each of the following, eliminate (theta) to give an equation relating x and y:
a) x = sin (theta), y = cos (theta)
x2 = sin2t , y2 = cos2t
x2 + y2 = 1
b) x = sin (theta), y = 2cos(theta)
x2 = sin2t , (y/2)2 = cos2t
x2 + y2/4 = 1
c) x = sin (theta), y = cos^2 (theta)
x2 = sin2t
x2 + y =1
d) x = sin (theta), y = tan (theta)
x2 = sin2t , y2 = sin2t / cos2t
cos2t = 1-sin2t
y2 = x2 / (1-x2)
e) x = sin (theta) + cos (theta), y = cos (theta) - sin (theta)
x + y = 2cost , x - y = 2sint
((x+y)/2)2 = cos2t , ((x-y)/2)2 = sin2t
(x+y)2 + (x-y)2 = 4
x2 + 2xy +y2 + x2 - 2xy + y2 = 4
2x2 + 2y2 = 4